Mapping the Limit of the Penobscot River Valley Calving Empayment, Hampden 7.5' Quadrangle, Maine - Olson, Jeffrey D. (My University, 2010)
The Penobscot River valley of south-central Maine is an area of moderate relief that underwent deglaciation ~14.5 ka. During deglaciation, sea water was ~100 m deep in the Penobscot valley in the Hampden area, and highlands in the southern part of the Hampden area were more than 100 m above the marine limit. Hughes et al. (1985) proposed that calving bays were important in the Gulf of Maine during deglaciation, but this idea has been controversial. According to Lowell (1994), a calving embayment did not develop in the Penobscot valley because the deep-water area was too narrow. Work in the Bangor area has revealed ice-flow convergence toward the Penobscot valley--strong evidence for a calving embayment (Syverson and A.H. Thompson, 2008). The purpose of this study was to seek ice-flow evidence for the former calving embayment immediately south of Bangor.
Color poster with text, images, and maps.
Keywords: Geology--Maine--Penobscot River Valley; Ice calving--Maine--Maps; Glacial epoch--Maine--Maps; Posters